An Magnetohydrodynamics Effect of Non-Newtonian Fluid Flows Over a Stretching/Shrinking Surface with CNT - Sneha, K. N.; Mahabaleshwar, U. S.; Nihaal, K. M.; Öztop, Hakan Fehmi (Springer Heidelberg, 2024)
In this study, carbon nanotubes, which serve as nanoparticles, are added to the basic fluid. By using a similarity transformation, the governing equations are converted into a set of ordinary differential equations (ODEs), which are then solved analytically. In order to simulate the flow and heat transfer behavior of carbon nanotubes, the Prandtl numbers for water and kerosene are 6.72 and 21, respectively. The precision of the analytical solution found in this study for the nonlinear flow of fluid containing carbon nanotubes is what makes it so beautiful. With the available experimental data, the proposed model is reliable. The main physical parameters for the Jeffrey fluid flow on the stretching/shrinking surface using carbon nanotubes are shown in tables and graphs and described in detail for the thermal and boundary layers. Carbon nanotubes enhance the heat more than the nanofluid; for this purpose, the work on carbon nanotubes flow through stretching/shrinking surfaces has many applications in biomedical, solar energy, generator cooling, nuclear system cooling, etc. Therefore, it is quite significant to assimilate the analytical extension of heat transfer fluid in the presence of magnetohydrodynamics under the influence of slip velocity. Further, carbon nanotubes can effectively elucidate the base materials' thermal performance and mechanical properties. Here, we assimilated the extension of heat transfer fluid in the incidence of magnetohydrodynamics under the influence of slip velocity analytically. Further, carbon nanotubes can successfully elucidate the base materials' thermal performance and mechanical properties.
Keywords: Jeffrey fluid flow; Magnetohydrodynamics; Slip velocity; Carbon nanotubes; Stretching/shrinking